Gender Inequality in Managing Childhood Sleep: Which Parent Gets up at Night? - Agnès Breton; Florian Lecuelle; Louise Chaussoy; Madeleine Heitz; Wendy Leslie; Royce Anders; Marie-Paule Gustin; Patricia Franco; Benjamin Putois (Children)
Objective: Parental responsibilities for childcare remain unequally distributed between mothers and fathers. This study investigates whether such gender disparity also applies to night-time care, particularly when children experience sleep disorders. Methods: We conducted a cross-sectional survey study including 882 clinical files from sleep consultations for children aged 0 to 5 years, completed by one parent (98% mothers). To assess inter-rater reliability, 112 father–mother dyads outside the clinical setting were also surveyed. Additionally, 1409 mothers from the general population formed a control group. Results: In the clinical group, 60% of children were cared for exclusively by their mother at night, versus 9% by the father. In the control group, the figures were 64% and 6%, respectively. Gender disparities persisted even when both parents worked full-time or when the child was no longer breastfed. Inter-rater reliability was strong (r > 0.70). Factors such as number of night awakenings, child’s age, and maternal education influenced caregiving distribution. Greater maternal involvement was associated with increased psychological distress and lower relationship satisfaction. Conclusions: Mothers remain the primary caregivers at night, even in dual-earner families. This unequal distribution can affect maternal well-being and couple dynamics. Promoting paternal involvement may reduce maternal overload and improve child sleep outcomes.